2015
DOI: 10.1037/xhp0000053
|View full text |Cite
|
Sign up to set email alerts
|

Failures of perception in the low-prevalence effect: Evidence from active and passive visual search.

Abstract: In visual search, rare targets are missed disproportionately often. This low-prevalence effect (LPE) is a robust problem with demonstrable societal consequences. What is the source of the LPE? Is it a perceptual bias against rare targets or a later process, such as premature search termination or motor response errors? In 4 experiments, we examined the LPE using standard visual search (with eye tracking) and 2 variants of rapid serial visual presentation (RSVP) in which observers made present/absent decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 59 publications
(95 reference statements)
12
92
0
Order By: Relevance
“…This has been seen in blue jays who will pass over less common prey while foraging for the more common (Bond & Kamil, 2002). Similar effects are seen in search when one target type is rarer than another (Godwin et al, 2015; Hout, Walenchok, Goldinger, & Wolfe, 2015). …”
Section: Resultsmentioning
confidence: 52%
“…This has been seen in blue jays who will pass over less common prey while foraging for the more common (Bond & Kamil, 2002). Similar effects are seen in search when one target type is rarer than another (Godwin et al, 2015; Hout, Walenchok, Goldinger, & Wolfe, 2015). …”
Section: Resultsmentioning
confidence: 52%
“…First, as specified in many theories (e.g., Duncan & Humphreys, 1989; Wolfe, 2007), visual search involves “resonance-seeking” between targets held in WM and objects in the environment (see also Hout, Walenchok, Goldinger, and Wolfe, 2015). When a person has a search target in mind, attention is drawn toward objects that resemble the target and perceptual processes evaluate those objects as potential matches.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of perceptual identification errors has been used as evidence against strict direct‐control accounts, with such occurrences being regarded as a natural by‐product of the fact that fixations can be terminated by an indirect mechanism (e.g., an autonomous timer) that drives fixations to new locations irrespective of whether or not the processing of an object at a given fixation location has been completed. However, more recent studies (Godwin, Menneer, Riggs, Cave, & Donnelly, ; Godwin et al., ; Hout et al., ) have found that perceptual identification errors are more likely to occur when the target is presented on a small proportion of trials (5% of trials) compared with a higher proportion of trials (45%), perhaps because of priming from target repetition and/or expectations about the likelihood of a target being presented (Godwin et al., ,b). This finding suggests that failures to detect the target upon fixating it may reflect object identification failures rather than being a consequence of some indirect mechanism, as predicted by indirect‐control accounts.…”
Section: A New Approach: Using Lag‐2 Revisits To Understand Trade‐offmentioning
confidence: 99%